CAPACITAÇÃO PARA A AFERIÇÃO DA PRESSÃO ARTERIAL DURANTE CONSULTA PEDIÁTRICA: INSTRUMENTO AO DIAGNÓSTICO PRECOCE DA HIPERTENSÃO INFANTO-JUVENIL - Vallandro, Claudia Funck (2017)
Blood pressure measure in children and adolescentes is recommended by relevant medical associations, but it isn´t performed in most of routine pediatric evaluations. Unknowing of its measure importance and specific thecnical questions are barriers for this procedure. This study aimed to capacitate and implement blood pressure measure in children and adolescents during routine evaluations in General Pediatric ambulatory of an educational hospital. A study was done using action-research as methodological tool for the professional capacitation. In conclusion, childhood arterial hypertension is a subject that is unnoticed, and health team that works with this social segment generally ignores it. With this study, it was possible to capacitate health professionals for blood pressure measurement during routine pediatric consultation, allowing the implementation of diagnostic triage routines, improving the medical assistance quality in health services.